Effects of dressing procedures upon yield and quality of the beef tenderloin - P.E. De Felicio; Dell M. Allen; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 1981)
Removing kidney fat at slaughter did not affect (P>.05) the chilled or chilled-and-aged weights of the tenderloin. But small differences in tenderness and color at the beginning of the display period favored the conventional dressing procedure.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Beef tenderloin; Yield grade; Quality grade